2021
DOI: 10.3390/molecules26072008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Molecular Degradation of Schizostachyum Brachycladum Bamboo Cellulose Nanofibre in PLA-Chitosan Bionanocomposites

Abstract: The degradation and mechanical properties of potential polymeric materials used for green manufacturing are significant determinants. In this study, cellulose nanofibre was prepared from Schizostachyum brachycladum bamboo and used as reinforcement in the PLA/chitosan matrix using melt extrusion and compression moulding method. The cellulose nanofibre(CNF) was isolated using supercritical carbon dioxide and high-pressure homogenisation. The isolated CNF was characterised with transmission electron microscopy (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 59 publications
0
26
0
1
Order By: Relevance
“…The three-dimension of the tissue scaffold should be adequately designed in terms of architecture as well as physicochemical properties. Some biopolymeric aerogels can dissolve in aqueous solution and transform into soft hydrogels and have been found to be good candidates to mimic some tissue environments [ 103 , 104 ]. Mahumane et al [ 105 ] suggested that the tissue scaffold should be designed with pores that are small enough to support three dimensions of cell–cell contacts and at the same time large enough to allow nutrients, oxygen, and bioactive factor diffusion to ensure the survival and growth of cells.…”
Section: Biopolymer-based Aerogels In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…The three-dimension of the tissue scaffold should be adequately designed in terms of architecture as well as physicochemical properties. Some biopolymeric aerogels can dissolve in aqueous solution and transform into soft hydrogels and have been found to be good candidates to mimic some tissue environments [ 103 , 104 ]. Mahumane et al [ 105 ] suggested that the tissue scaffold should be designed with pores that are small enough to support three dimensions of cell–cell contacts and at the same time large enough to allow nutrients, oxygen, and bioactive factor diffusion to ensure the survival and growth of cells.…”
Section: Biopolymer-based Aerogels In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Compared with other aliphatic polyesters, PLA has excellent properties, such as mechanical strength, high modulus, biodegradability, biocompatibility, bioabsorbability, transparency, low toxicity, and ease of manufacturing process [ 22 , 141 , 142 ]. Due to these properties, PLA has many applications, such as agricultural films, biomedical devices, packaging, and the automotive industry [ 10 , 143 , 144 ].…”
Section: Antimicrobiological Packagingmentioning
confidence: 99%
“…A good example of using PLA to create films with antimicrobial properties is its combination with chitosan [ 15 , 142 ]. PLA also obtains better mechanical properties and better barrier properties.…”
Section: Antimicrobiological Packagingmentioning
confidence: 99%
See 2 more Smart Citations